2023
DOI: 10.3390/foods12071560
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Aroma Profiles of Guangdong Black Teas Using Non-Targeted Metabolomics

Abstract: Guangdong black teas have diverse flavors and aromas. To explore the molecular basis of these aromas, we extracted and analyzed the volatile flavor compounds of 31 black tea samples from 7 districts (Yingde, Luokeng, Renhua, Meizhou, Chaozhou, Lianshan, and Heyuan) in Guangdong Province with headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography–mass spectrometry (GC–MS). Then, 135 volatile flavor compounds (VFCs) were identified and grouped into 12 classes according to their chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have found that the tea cultivars, processing techniques, and environmental conditions could influence the aroma of black tea [24]. For example, the Xinyang black tea has a sugary honey-like aroma [24], Keemun black tea has a distinct rose aroma/Keemun aroma [25], Sichuan black tea has a sweet and citrus-like aroma [26], Guangdong black tea has a sweet and floral aroma [27], and Jinxuan (Oolong tea cultivar) black tea possesses a higher floral aroma [28]. In this study, the aroma of Taishan black tea was mainly fruity, followed by a caramel, sweet aroma, with a strong and enduring fragrance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the tea cultivars, processing techniques, and environmental conditions could influence the aroma of black tea [24]. For example, the Xinyang black tea has a sugary honey-like aroma [24], Keemun black tea has a distinct rose aroma/Keemun aroma [25], Sichuan black tea has a sweet and citrus-like aroma [26], Guangdong black tea has a sweet and floral aroma [27], and Jinxuan (Oolong tea cultivar) black tea possesses a higher floral aroma [28]. In this study, the aroma of Taishan black tea was mainly fruity, followed by a caramel, sweet aroma, with a strong and enduring fragrance.…”
Section: Discussionmentioning
confidence: 99%
“…There's a Chinese proverb that describes white tea as “one-year tea, three-year medicine, seven-year treasure” indicating that storage significantly influences the taste, aroma, chemical composition, and health benefits of white tea. Moreover, stored white tea often holds higher commercial value ( Wang et al, 2023 , Wang et al, 2023 ). During the storage period, notable changes occur: herbal and sweet aromas become more pronounced while green and grassy notes diminish ( Qi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the relationship between the chemical components of white tea and its origin and storage duration remains unclear. As the application of metabolomics in the study of tea quality chemistry becomes increasingly widespread and enables the quantification of a plethora of compounds in tea ( Shan et al, 2023 , Wang et al, 2023 , Wang et al, 2023 , Zhou et al, 2022 ), the need for a high-throughput method to identify compounds associated with the tea's origin and storage duration has arisen. Therefore, this study utilizes a metabolomics approach, employing an ultra-high-performance liquid chromatography-quadrupole/electrostatic field orbitrap mass spectrometer (UHPLC-Q-Exactive/MS), to analyze Baimudan grade I samples from diverse origins and varying storage durations, aming to unveil the links between the chemical components in white tea, its origin, and the duration of storage.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics, a rapidly advancing technology, has significantly contributed to plant-related sciences and drug discovery [ 21 ]. Non-targeted metabolomics analysis, utilizing high-resolution mass spectrometry, allows for the unbiased measurement of metabolite [ 22 , 23 ]. Previous studies have explored metabolic changes in Salvia miltiorrhiza during post-harvest processing using a metabolomics approach to identify the optimal processing method [ 24 ].…”
Section: Introductionmentioning
confidence: 99%